General Considerations in Managing Non- Odontogenic Orofacial Pain: Life sciences-Medicine - R. Sonar, Dr. Prasanna; S. Panchbhai, Dr. Aarati (International Journal of Life Science and Pharma Research, 2023)
Orofacial pain is characterized as facial and mouth discomfort. The most prevalent inflammatory pain to appear inthis area is dental pain. However, chronic pain illnesses, such as temporomandibular joint disorders, primary headaches(neurovascular), neuropathic pain, and idiopathic pain, can commonly mimic toothaches. Dentistry’s specialty in orofacial painfocuses on diagnosing and treating persistent, complicated facial pain and oromotor disorders. This area of dentistry has grownthroughout time due to the desire to comprehend better a group of patients who, for some reason, were not experiencingtooth pain issues. Orofacial discomfort has a major impact on morbidity and the use of medical services. Several illnesses cancause orofacial discomfort; diagnostic uncertainty is commonly seen in clinical practice. Due to their varying pain presentation,toothaches can resemble many chronic episodic orofacial pain syndromes, leading to many improperly prescribed antibioticregimens and surgical treatments. Ear, nose, throat, and maxillofacial surgeons also fall victim to the misdiagnosis, making themnot the only professionals to suffer from it. The orofacial region’s complex diversity makes it difficult for doctors to handle nonodontogenic pain with an oral origin. The physician must be well-versed in the many pain problems affecting the orofacial areaand the various alternatives accessible for their best care to provide a precise diagnosis and successful treatment. This paperfocuses on the different types of pain, characteristics, assessments, investigations, and general considerations in managing nonodontogenic pain of the orofacial region. To adequately manage these patients, our profession has come to understand howimportant a fundamental understanding of orofacial pain is. Many improvements have been brought about by this adjustment inthe approach in both clinical and educational settings. This review covers all general aspects of orofacial pain management.